Analysis of the Causes and Crisis of Global Warming - Fang Hanyu (MATEC Web of Conferences, 2023)
The problem of global warming has become more and more serve recently. People around the world start to be affected by the result of this problem. Global warming affects the environment by causing different disasters, taking up the habitat that available to organisms, and making the environment too harsh to support organisms’ survival. Global warming impact human being by reducing the food production and resources so that increases the competition. In addition, the disasters induced by this problem also harm people. In order to come out the solution to fix the problem, it should focus on the causes of global warming. The intensive greenhouse effect is the main cause of the global warming. Moreover, the swelling sun, and resultant stronger solar radiation, and several positive feedback loops also contribute to form the global warming problem. In this case, people came out different solutions from four different aspects: policy, biological, geological, and chemical aspect.